2002
DOI: 10.1016/s0969-2126(02)00723-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure of NF-κB p50/p65 Heterodimer Bound to the PRDII DNA Element from the Interferon-β Promoter

Abstract: Upon viral infection, NF-kappaB translocates to the nucleus and activates the IFN-beta gene by binding to the PRDII element. Strikingly, NF-kappaB loses its ability to activate the IFN-beta gene when the PRDII element is substituted by closely related sites. We report here the crystal structure of NF-kappaB p50/p65 heterodimer bound to the PRDII element from the IFN-beta promoter. The structure reveals an unexpected alteration in configuration, in which the p50 specificity domain moves by as much as approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 38 publications
2
62
2
Order By: Relevance
“…X-ray structure determination of a p50:p65/RelA RHR heterodimer bound to kB DNA from the original k light chain gene promoter, which is identical to a kB sequence that is present in the promoter of HIV genome (5 0 -GGGAC T TTCC-3 0 ), served to confirm this speculation (Chen et al 1998a). Additional crystal structures of NF-kB p50: p65/RelA heterodimer bound to different kB DNA further support the basic rules of DNA half-site recognition developed from the homodimer:DNA structures (Berkowitz et al 2002;Escalante et al 2002).…”
Section: Nf-kb Dimerizationmentioning
confidence: 70%
“…X-ray structure determination of a p50:p65/RelA RHR heterodimer bound to kB DNA from the original k light chain gene promoter, which is identical to a kB sequence that is present in the promoter of HIV genome (5 0 -GGGAC T TTCC-3 0 ), served to confirm this speculation (Chen et al 1998a). Additional crystal structures of NF-kB p50: p65/RelA heterodimer bound to different kB DNA further support the basic rules of DNA half-site recognition developed from the homodimer:DNA structures (Berkowitz et al 2002;Escalante et al 2002).…”
Section: Nf-kb Dimerizationmentioning
confidence: 70%
“…Among these, Arg35 and Glu39 are known to be involved in the interaction with DNA bases, and Cys38 and Arg187 are involved in binding with the sugar phosphate backbone (Chen et al, 1998b;Escalante et al, 2002). Chain A denotes the p65 subunit; chain B denotes the p50 subunit; chain C denotes the IkBz chain.…”
Section: Discussionmentioning
confidence: 99%
“…A strict sequence requirement for NF-nB inducibility is observed in the nB site within the IFN-h promoter (GGGAAATTCC), which when substituted by a closely related nB site from the Ign light gene enhancer (GGGACTTTCC) becomes nonresponsive to NF-nB activation (12). Structural studies revealed that differences in nB sequences of IFN-h and the Ign light chain gene enhancers contribute to structural changes in the NF-nB dimer/DNA complex, leading to altered gene expression (13,14). Leung et al (11) showed that the nB site sequence specifies which coactivators will result in productive interactions with bound NF-nB dimers.…”
Section: Introductionmentioning
confidence: 99%